APPLICATION OF AUTO-REGRESSIVE MOVING-AVERAGE (ARMA) METHOD FOR STRUCTURAL DYNAMIC MODAL PARAMETERS IDENTIFICATION IN TIME DOMAIN - Bernadus Nicholas, Ignatius
Dynamic loading test is one of the testing methods to obtain structural dynamic response. Structural dynamic modal parameters can be obtained through post processing of dynamic structure response data using modal analysis method. Modal analysis method can be classified into two, namely, modal analysis in frequency domain and modal analysis in time domain. Auto Regressive Moving Average (ARMA) method is one of modal analysis method in time domain. ARMA method has advantages compared to conventional Peak Picking method, where analysis methods can use response data either from known excitation sources or from environmental excitation.